A new device for measuring forces in the footrest during on-water kayaking. (December 2022) - Klitgaard, Kent K; Hansen, John; de Zee, Mark
Several studies have investigated paddle force on the water. However, a limited number of studies have investigated on-water footrest forces. The purpose of this study was to design, implement, and validate a device which measures forces applied to the footrest during on-water kayaking without hindering the athletes' performance. A Nelo footrest was modified and equipped with two load cells. The footrest was calibrated by loading it with known weights perpendicular to the surface of the footrest. A portable custom-built data acquisition system was built. The data acquisition system was placed in a box behind the seat in the kayak. The system was able to measure the paddling technique related to the legs during on-water testing and distinguish between different intensities. The system developed in the current study can help to improve kayak sprint performance in new ways, as the system elucidates forces within the kayak. Moreover, the system can provide clarification of the biomechanical aspects of the leg push during sprint kayaking.